Systemic Catheter-Related Venous Thromboembolism in Children: Data From the Italian Registry of Pediatric Thrombosis - Lasagni, Donatella; Nosadini, Margherita; Molinari, Angelo Claudio; Saracco, Paola; Pelizza, Maria Federica; Piersigilli, Fiammetta; Putti, Maria Caterina; Gaffuri, Marcella; Giordano, Paola; Lorenzoni, Giulia; Francavilla, Andrea; Trapani, Sandra; et al. (Frontiers in Pediatrics, 2022)
Background. Central venous catheters (CVCs) represent one of the main risk factors for venous thrombotic events (VTEs) in children. Methods. We studied the Italian Registry of Pediatric Thrombosis (RITI) with regards to systemic radiologically-confirmed CVC-related VTEs (CVC-VTEs) occurred during 6.5 years in children aged 29 days to 18 years. Results. 78 CVC-VTEs were included, occurred in 76 patients (40/76, 53% males). CVC-VTEs comprised 67 non-cardiac VTEs (86%) and 11 intracardiac thrombotic events (ICTEs) (14%); median age at onset was 19 months and 17 months, respectively. The most frequent reason for CVC insertion was supportive therapy. The catheters were placed percutaneously in 85% of cases (56/66), and surgically in the remaining 15% (10/66). Peripherally inserted central catheters (PICC) were used in 47% (31/66) cases, partially implanted catheters in 42% (28/66), non-implantable catheters in 7% (5/66), and totally implanted (Port) in 2% (1/66). CVC-VTEs were symptomatic in 77% of cases (60/78), while in the remaining 23% they were incidentally detected on imaging performed for the underlying condition. Median time between CVC insertion and onset of symptoms was 10 days in non-cardiac VTEs and 39 days in ICTEs. Doppler ultrasound was the diagnostic technique most frequently used. The venous compartment most frequently affected were the veins of the lower extremities (52%, 43/73). Anti-thrombotic treatment was administered in 96% of CVC-VTEs (75/78). 2.6% (2/76) of patients experienced a second thrombotic event. At discharge, post-thrombotic syndrome was reported in 13.5% (5/37) events with available data, CVC replacement in 10.8% (4/47), and ischemic necrosis with toe finger amputation in 2.7% (1/37). Three patients died due to the underlying condition; no CVC-VTE-related deaths were reported. Conclusions. We have carried out a registry-based study on CVC-VTEs in children in Italy, providing data that may help improve detection and management of this CVC-related complication.